Internet of Things framework for enhancing electronic health record retrieval for Malaysian pilgrims - Ali Ibrahim Latif (2023)
The rise of global travel has increased the number of travelers who are exposed to illnesses in their destination country. Some problems arise during health care delivery at destination as they receive healthcare as non-local patients. When treating non-local patients, healthcare providers need access to the health record of those patients to determine their medical history and any chronic or inherited diseases. Electronic health record (EHR) systems are only effective for local healthcare services within the patient’s country. Therefore, an effective EHR method should be adopted to support the global healthcare needs of travelers. The Internet of Things (IoT) technology is an effective solution to accomplish real-time retrieval of historical EHRs. In a pilgrimage environment such as the Hajj, IoT can be applied by identifying non-local patients through electronic tags; the tag data can be read with wireless sensors. The data collected using radio-frequency identification can be acquired from a wireless sensor network to accomplish many decisions, such as sending an ambulance to a patient’s location, sending an emergency alert to this patient’s immediate family circle, and retrieving the patient’s EHR from a database. This research aims mainly to develop an IoT framework for real-time retrieval of Malaysian pilgrims’ EHRs from a database in Malaysia by the Kingdom of Saudi Arabia’s (KSA) healthcare facilities over the Internet. The sub-objectives for achieving the main research objective are as follows: identifying the most useful structure, facilities, and components of the proposed IoT framework; analyzing the challenges, importance, and viability of EHR retrieval using IoT from the Malaysian and KSA perspectives; and identifying the technical issues of IoT and pilgrims’ EHRs that are required to formulate the proposed framework. To generate integrative conclusions from a multiple methods study, we adopted a triangulation method of developing the framework. The data collection methods included: questionnaire (close-ended and open), observation, and focus group discussion. The proposed framework was developed on the basis of the collected data and was validated by Malaysian experts. Results confirmed participants’ support of the framework and identified salient features of effective framework. The validation results showed that the proposed framework can support the healthcare needs of Malaysian pilgrims. This research mainly contributes by developing an IoT framework for supporting non-local patients through the retrieval of EHRs between countries via the Internet network.